The Samaritan's Dilemma: The Political Economy of Development Aid - Gibson, Clark C.; Andersson, Krister; Ostrom, Elinor; Shivakumar, Sujai (Oxford University Press, 2005)
What's wrong with foreign aid? Many policymakers, aid practitioners, a nd scholars have called into question its ability to increase economic growth, alleviate poverty, or promote social development. At the macr o level, only tenuous links between development aid and improved livin g conditions have been found. At the micro level, only a few programs outlast donor support and even fewer appear to achieve lasting improve ments. The authors of this book argue that much of aid's failure is re lated to the institutions that structure its delivery. These instituti ons govern the complex relationships between the main actors in the ai d delivery system and often generate a series of perverse incentives t hat promote inefficient and unsustainable outcomes. In their analysis, the authors apply the theoretical insights of the new institutional e conomics to several settings. First, they investigate the institutions of Sida, the Swedish aid agency, to analyze how that aid agency's ins titutions can produce incentives inimical to desired outcomes, contrar y to the desires of its own staff. Second, the authors use cases from India, a country with low aid dependence, and Zambia, a country with h igh aid dependence, to explore how institutions on the ground in recip ient countries also mediate the effectiveness of aid. Throughout the b ook, the authors offer suggestions about how to improve aid's effectiv eness. These suggestions include how to structure evaluations in order to improve outcomes, how to employ agency staff to gain from their on -the-ground experience, and how to engage stakeholders as "owners" in the design, resource mobilization, learning, and evaluation processes of development assistance programs.